Endoscopic Management of a Rare Intraluminal Duodenal “Windsock” Diverticulum Causing Recurrent Pancreatitis - Ozturk, Oguz; Cagir, Yavuz; Durak, Muhammed Bahaddin; Ergul, Mucahit; Atay, Ali; Yuksel, Ilhami (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Ozturk O, Cagir Y, Durak MB, Ergul M, Atay A, Yuksel I. Endoscopic management of a rare intraluminal duodenal “windsock” diverticulum causing recurrent pancreatitis. Turk J Gastroenterol. Published online October 31, 2025. doi:10.5152/ tjg.2025.25051.